2008
DOI: 10.3390/molecules13040779
|View full text |Cite
|
Sign up to set email alerts
|

A Microwave-Assisted and Heteropolyacids-Catalysed Cyclocondensation Reaction for the Synthesis of 4(3H)-Quinazolinones

Abstract: We have investigated a microwave–assisted synthesis of 4(3H)–quinazolinones by condensation of anthranilic acid, orthoesters (or formic acid) and substituted anilines, using Keggin-type heteropolyacids (H3PW12O40∙13H2O, H4SiW12O40∙13H2O, H4SiMo12O40∙13H2O or H3PMo12O40∙13H2O) as catalysts. We found that the the use of H3PW12O40∙13H2O acid coupled to microwave irradiation allows a solvent-free, rapid (~13 min) and high-yielding reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…NMR spectra of aminoquinazolinones (presented in figure 6) in CDCl 3 showed a singlet of 3 protons of methyl group at 2.6 , singlet of 2 protons of primary amino group at 4.8 and an aromatic multiplet in the region between 7.1 -8.1 . Moreover, structure of quinazolinone elucidated by NMR spectroscopy evidents that quinazolinone is a linear molecule because of 13 C signal corresponding to the carbonyl carbon, C4, exists as a doublet with J CH = 3.0 Hz. This is indicative of coupling through 3 bonds, a condition that is met by the 4(3H)-quinazolinone but not with an angular 4-(1H)-quinazolinone [12].…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectra of aminoquinazolinones (presented in figure 6) in CDCl 3 showed a singlet of 3 protons of methyl group at 2.6 , singlet of 2 protons of primary amino group at 4.8 and an aromatic multiplet in the region between 7.1 -8.1 . Moreover, structure of quinazolinone elucidated by NMR spectroscopy evidents that quinazolinone is a linear molecule because of 13 C signal corresponding to the carbonyl carbon, C4, exists as a doublet with J CH = 3.0 Hz. This is indicative of coupling through 3 bonds, a condition that is met by the 4(3H)-quinazolinone but not with an angular 4-(1H)-quinazolinone [12].…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Both 1 H and 13 C NMR have been employed as important tools to confirm the structures of the derivatives as well as regioselective isomers. Gursoy et al evaluated the 1 H-NMR spectra in DMSO-d 6 and revealed the existence of two isomers.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…For the preparation of 2,4(1H,3H)-quinazolinediones and 2-thioxoquinazolinones in drug discovery efforts, Liu and co-workers [120] investigated a simple process for access of the quinazoline moiety from commercially available methyl and substituted iso(thio)cyanates. Under microwave irradiation, the short reaction time (20 min) and mild reaction conditions ( O) coupled to microwave irradiation allowed a solventless, rapid (13 min) and high-yielding preparation of 4(3H)-quinazolinones by condensation of anthranilic acid, aniline, and an orthoester (or formic acid) [121]. A series of novel 2,4-disubstituted quinazoline-based chemical entities as potent Pin1 inhibitors with IC 50 values at the micromolar level were synthesized in high yield from anthranilic acids and urea under microwave irradiation [122].…”
Section: Synthesis Of Quinazolines and Related Compoundsmentioning
confidence: 99%
“…A series of methods has been developed previously for the synthesis of 3-substituted 4(3H)-quinazolinones from anthranilic acid, orthoesters, and amines in the presence of various catalysts [1][2][3][4][5][6][7][8]. The drawbacks of these methods are expensive catalyst, high temperature (60-80 o C), long reaction time (20 h), etc.…”
mentioning
confidence: 99%